RADI-05. EVALUATION OF THE IMPLEMENTATION OF THE RANO CRITERIA IN THE HERBY TRIAL OF PEDIATRIC PATIENTS WITH NEWLY DIAGNOSED HIGH-GRADE GLIOMAS. Issue 2 (22nd June 2018) - Rodriguez, Daniel; Morgan, Paul; Warren, Daniel; Warmuth-Metz, Monika; Aliaga-Sanchez, Esther; Calmon, Raphael; Jones, Chris; Varlet, Pascale; Hargrave, Darren; Cañete, Adela; Massimino, Maura; Azizi, Amedeo; et al.
Abstract: INTRODUCTION: The purpose of this study was to evaluate the implementation of the radiological aspects of HERBY trial, and the practicality and feasibility of including multimodal imaging (MMI) to the response assessment in neuro-oncology (RANO) criteria in a pediatric high grade glioma cohort. METHODS: We analyzed MMI compliance rates and scan quality for participating sites, adjudication rates and reading times for the central review process, the influence of the different RANO criteria in the final response, and the benefit of incorporating MMI to the decision process. RESULTS: MMI compliance rates were: diffusion 82%, perfusion 60% and spectroscopy 48%. Of the received data 2% of the structural scans and 23% of the MMI scans were not of sufficient quality. Adjudication rates due to differing neuroradiologist responses were 50%, which resulted in a total average reading time per patient of 3 hours. Increase in diameters of the target enhancing lesion was a reason for progression in 8/86 cases (9.3%) but never the only radiological or clinical reason. EFS was predicted earlier in 5/86 (5.8%) patients by MMI (diffusion, n=4; perfusion, n=1). CONCLUSION: The addition of MMI to the response criteria was difficult to assess due to low return rates and data quality, but MMI helped to determine progression prediction than structural imaging alone. Increase of target lesion diameter measurement, which accounts for a large proportion of reading time, was never the only reason to stablish disease progression.